An Event-Related Potential Study on Facial Recognition in Children with and without Autism Spectrum Disorders - Deng JR; Tong M; Zhang XT; Lin ZP; Wang Z; Long J; Chen ZM (Neuropsychiatric Disease and Treatment)
Jia-Rui Deng,1 Meiqinzi Tong,1 Xiao-Tong Zhang,1 Zhen-Ping Lin,1 Zhuo Wang,2 Jinyi Long,3 Zhuo-Ming Chen1 1Department of Rehabilitation Medicine, The First Affiliated Hospital of Jinan University, Guangzhou, Guangdong Province, People’s Republic of China; 2Wellness Technology Research Center, Hefei Intelligent Robot Institute, Hefei, Anhui Province, People’s Republic of China; 3College of Information Science and Technology, Jinan University, Guangzhou, Guangdong Province, People’s Republic of ChinaCorrespondence: Zhuo-Ming Chen, Department of Rehabilitation Medicine, The First Affiliated Hospital of Jinan University, No. 613, West Huangpu Avenue, Tianhe District, Guangzhou, Guangdong Province, 510632, People’s Republic of China, Email tchzm@jnu.edu.cn Jinyi Long, College of Information Science and Technology, Jinan University, Guangzhou, Guangdong Province, People’s Republic of China, Email jinyil@jnu.edu.cnPurpose: Facial recognition is very primary and important in individuals’ development and the event-related potential based on face recognition such as N170 is considered as the most potential objective marker of autism, the hot and difficult point of current research. We will explore the electrophysiological basis of facial recognition with autism and without autism. Given the link between facial recognition and social impairments, the core symptom of autism, it is also necessary to study the correlation between the P1 and N170 components and the severity of social functioning in autism.Patients and Methods: In this study, autism and age-matched typically developing children were asked to examine photographs of faces, objects and butterflies and event-related potentials were recorded. The parents or caregivers of the participants were asked to fill out the Vineland Adaptive Behavior Scale. Finally, thirteen children with autism (6.60± 2.12years) and ten typically developing (6.65± 1.64years) children were included in the experiment.Results: Children with autism showed slower P1 and N170 latencies than typically developing children. The N170 amplitude for faces was larger than that for objects. Considering age as a covariant, the results primarily remained unchanged and the effect size of age was significant for the P1 and N170 latencies. As for the correlation between ERPs and the severity of social impairment, there were some significant correlations between the P1 and N170 latencies and social functioning.Conclusion: This result not only suggests the electrophysiological basis of facial recognition but also indicates that the P1 and N170 components could assist in the diagnosis and assessment of autism. Moreover, the results suggest that age should be considered in analyses of the P1 and N170 latencies. Due to a limited number of participants, conducting a multi-center and large-sample study in the future is necessary.Keywords: ASD, N170, P1, EEG, age, social functioning